Children with Type 1 Diabetes Mellitus and their friends: the influence of this interaction in the management of the disease (Revista Latino-Americana de Enfermagem, 2012)
Friends' support is a key element in the management of Type 1 Diabetes Mellitus. This study describes the influence of friends on the lives of children with Diabetes Mellitus and its implications for managing the disease. Empirical data were collected through semi-structured interviews, supported with the use of puppets, with 19 children aged between seven and 12 years old. The qualitative analysis of the testimonies allowed understanding the phenomenon from two perspectives: the attitude of friends towards the child, positively or negatively affecting the disease's management, and the attitude of the child toward friends. The knowledge of those involved and the interaction between the children with DM1 and their friends impacts the management of the disease. Understanding the implications of these interactions contributes to the delivery of qualified nursing care to this population.